IMPLEMENTASI BALANCED SCORECARD UNTUK MENINGKATKAN KINERJA ORGANISASI - ENDRA YAMAN LINARDI (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2014)
The purpose of this study was to evaluate the implementation of the Balanced Scorecard performance improvement organization of PT Matahari Putra Prima, especially at SBU Supermarket. Reviews of the 6th KPI describe the progress or deterioration that has been achieved by MSM in the 10-month period since the BSC is implemented in January 2004. From the financial period Oct 2003 to Oct, 2004, MSM much progress.